Annual performance of solar tower aided coal-fired power generation system. (15th January 2017) - Zhu, Yong; Zhai, Rongrong; Qi, Jiawei; Yang, Yongping; Reyes-Belmonte, M.A.; Romero, Manuel; Yan, Qin
Abstract: Solar tower aided coal-fired power generation system (STCG) is able to provide high solar utilization efficiency with low coal consumption rate. This paper compares performances of a solar tower aided coal-fired power plant, a solar tower power plant and a coal-fired power plant under different operative conditions. The comparison includes various solar multiple and thermal energy storage size. According to solar radiation resource and grid power dispatching demand, STCG, solar tower power generation system (STG) and coal-fired power generation system (CPG) work under off-design conditions all the year around. Results show that STCG has higher solar utilization efficiency than STG and lower coal consumption rate and CO2 emission rate than CPG. In addition, solar-to-electricity exergy efficiency of STCG is at least 1.83% higher than that of STG. Compared to CPG, the 1000 MWe STCG can reduce coal consumption by 2.0 × 10 5  t/y, with the saving ratio being 10.4%. The annual average coal consumption rate of STCG is 27.3 g/kWh lower than that of CPG. In addition, the annual average CO2 emission rate of STCG is reduced by 10.1% compared with that of CPG. Solar tower aided coal-fired power generation can facilitate energy conservation and emission reduction of STG and CPG. Highlights: Annual performance of STCG under off-design conditions is studied. STCG has a higher solar utilization efficiency than solar tower power plant. STCG has a lower coal consumption rate and CO2 emission rate than coal-fired plant. STCG shows a great potential in energy conservation and emission reduction.